Characteristics of Coronial Autopsy Cases in the London Area of the United Kingdom, Pre and Post COVID-19 Lockdown. Issue 1 (March 2023) - Bates, Alan W. H.
Introduction: In order to reduce transmission of COVID-19, in March 2020 the UK national and devolved governments imposed restrictions including spatial distancing, stay-at-home orders, and travel restrictions. The aim of this study is to compare the characteristics of cases referred to the Coronial system for autopsy in the months before and during the lockdown period. Methods: In all, 580 autopsy cases, performed in the London area between January and June 2020 were included in the study. Results: In the postlockdown period, there was an increase in the proportion of black individuals referred for autopsy, which just attained statistical significance ( p = 0.047). The proportion of decomposed bodies submitted for examination was significantly increased ( p = 0.011). The study did not show a significant increase in the proportion of out-of-hospital (community) deaths, traumatic deaths, or deaths due to alcohol or drug abuse or overdose. Conclusion: The study shows no evidence that COVID-19 preventative measures led to a change in the causes of death referred to the Coroner, except, of course, for COVID-related deaths. The proportion of black people among subjects for autopsy increased, probably because of a relatively higher incidence of COVID deaths among this group. Decomposed subjects were more common, probably due to social isolation.